a-6=-21

Simple and best practice solution for a-6=-21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for a-6=-21 equation:


Simplifying
a + -6 = -21

Reorder the terms:
-6 + a = -21

Solving
-6 + a = -21

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + a = -21 + 6

Combine like terms: -6 + 6 = 0
0 + a = -21 + 6
a = -21 + 6

Combine like terms: -21 + 6 = -15
a = -15

Simplifying
a = -15

See similar equations:

| x^2-2x+13=10x-7 | | -3x+21=7x-9 | | 9x-15=2x+34 | | 2x+12=6x-24 | | 8x+2=3x+27 | | 4=7x-10 | | 4(7-x)=5(x-2) | | 4x+9=51-2 | | 5-7x=37+4x | | 30+x=9x-10 | | 7a+10=-3a | | 48-3x=6x+17 | | (k+2)2w^2+4w+6=0 | | 193-6x=6x+30 | | 5*x+16*y=789 | | 6x-3=15x | | 2(i-3)=14 | | 6p=3p+30 | | 2g-3=1 | | 6x-4=3x+10 | | 3x+5-(2x+1-(2x-3-(x-2)))=x+15 | | 106-5x=22+22 | | 3u^2=11u+4 | | 4a+8=6(a+4) | | 17x+4y=67 | | 30-3x=6-3x | | 3a+4b=12 | | 3x-3v=3t | | x^2+14x=4 | | .5x=12+2x | | 6x+10=78x+x | | -17+-10*x=10+23 |

Equations solver categories